International Year of Planet Earth 6. Biosignatures: Interpreting Evidence of the Origins and Diversity of Life - Slater, G. F. (Geoscience Canada, 2009)
Biosignatures are molecular, mineral or isotopic patterns that can be unambiguously interpreted as evidence of life and so provide the means for us to address our most fundamental questions about the origins and evolution of life. Biosignatures of microbial life are especially important to our understanding of early Earth history, and can be recorded in magnetic mineral traces, various carbon compounds, and stable isotope ratios of many elements. These signatures, preserved in the geologic record, represent the primary means by which we gain insight into the early history of life on Earth, including the timing of the origins of life and major interactions of life with its environment, such as the oxidation of the Earth’s atmosphere. In addition, microbial biosignatures are also considered one of the most likely targets in the search for life beyond Earth. However, identifying and interpreting geochemical biosignatures of microbial life is challenging and involves careful differentiation between signatures of biological processes and those of abiological processes. Canada is playing an important role in biosig-nature research, both through the geologic record of life preserved in our ancient rocks, and through many examples of microbial life in extreme environments. The latter provide the modern understanding required to interpret the biosignature record from early Earth and perhaps one day from another planet. SOMMAIRE Les biosignatures sont ces arrangements moléculaires, minéraux et isotopiques qui sont des preuves évidentes de l’existence de vie organique, et qui sont donc autant de moyens nous permettant de tenter de répondre aux questions fondamentales sur l’origine et l’évolution de la vie. Les biosig-natures microbiennes sont particulièrement importantes pour la compréhension des premiers stades de l’histoire de la Terre; elles sont constituées de traces de minéraux magnétiques, de composés organiques divers, ou de ratios particuliers d’isotopes stables de nombreux éléments. Ces signatures conservées dans la roche sont des indicateurs de première importance nous permettant de déchiffrer les premiers stades de l’histoire de la vie sur Terre, incluant la chronologie des origines de la vie et des grandes interactions de la vie avec l’environnement, comme l’oxydation de l’atmosphère terrestre. De plus, on considère que les biosignatures microbiennes sont l’un des indicateurs les plus probables de la présence de vie extraterrestre. Cela dit, l’identification et l’interprétation de biosignatures géochimiques microbiennes est délicate; il faut pouvoir distinguer les biosignatures de processus biologiques de celles de processus abiologiques. Le Canada joue un rôle important dans la recherche sur les biosignatures, à la fois par les traces de vie préservées dans les roches anciennes de son histoire géologique, et du fait des exemples de vie microbienne dans des environnements extrêmes de son territoire. Les recherches en milieux extrêmes nous permettent d’acquérir les connaissances nécessaires pour interpréter les biosignatures des premiers stades de l’histoire géologique de la Terre, et peut-être un jour d’une autre planète.